Predictive power of isolated high home systolic blood pressure for cardiovascular outcomes in individuals with type 2 diabetes mellitus: KAMOGAWA-HBP study - Hosomi, Yukako; Ushigome, Emi; Kitagawa, Nobuko; Kitagawa, Noriyuki; Tanaka, Toru; Hasegawa, Goji; Ohnishi, Masayoshi; Tsunoda, Sei; Ushigome, Hidetaka; Nakamura, Naoto; Asano, Mai; Hamaguchi, Masahide; et al. (Diabetes & vascular disease research, 2023)
Aims/Introduction Isolated high home systolic blood pressure (IHHSBP) is a risk for cardiovascular disease (CVD). However, no study has shown an association between IHHSBP and CVD in diabetes. We examined the association between IHHSBP and CVD in type 2 diabetes. Materials and Methods This retrospective cohort study included 1082 individuals with type 2 diabetes, aged 20 to 90 years, without a history of macrovascular complications. Home blood pressure (HBP) was measured three times every morning and evening for 14 days. Cox proportional hazards models were used to examine the relationship between IHHSBP and CVD incidence. Results With the normal HBP group as the reference, the adjusted hazard ratio (HR) (95% confidence interval [CI]) for CVD was 1.58 (1.02–2.43) in the IHHSBP group. Correcting for antihypertensive medication use did not change HR. Based on sex, the adjusted HR (95% CI) for CVD was 1.25 (0.74–2.13) in males and 2.28 (1.01–5.15) in females. Conclusions In individuals with type 2 diabetes, those with IHHSBP had a higher HR for cardiovascular disease than those with normal HBP. But, Isolated high home diastolic blood pressure and high HBP were not. The association between IHHSBP and CVD was stronger in females than in males.